OC-050 Panenteric capsule endoscopy: whole gut visualisation without intubation. (22nd June 2015) - Hale, MF; Drew, K; Ejenavi, E; Sidhu, R; McAlindon, ME
Abstract : Introduction: Capsule endoscopy (CE) is a well-tolerated, first line small bowel (SB) investigative modality. A specifically adapted version is available to image the colon, thus providing an option for non-invasive, single visit imaging of the entire gastrointestinal tract. This study evaluates a novel panenteric protocol utilised to investigate patients with symptoms which could originate from the SB, large bowel or both sites. Method: Retrospective, single centre, involving consecutive patients attending for panenteric CE between July 2008 and December 2014. PillCam SB (Given Imaging, Israel) or MiroCam (Intromedic, Korea) and PillCam Colon 2 (Given Imaging) were used. All patients with known inflammatory bowel disease (IBD) successfully passed a PillCam Patency device prior. Patient demographics, procedural data, final diagnosis and outcomes were collected. Results: 108 procedures were performed, mean age 41.5 years (range 16–95), 72 female, median follow up 27 months (range 2–79). 41 patients had known IBD (37 Crohn's, 4 ulcerative colitis (UC)) and were undergoing disease re-assessment after 12 months of anti-TNF therapy (12), or due to relapse in symptoms (29). The remaining 67 patients had suspected IBD with predominant symptoms of diarrhoea (33), abdominal pain (15), iron deficiency anaemia (8), weight loss (6) and gastrointestinal bleeding (5). 51 patients refused colonoscopy, 37 chose CE over colonoscopy, 17 had an incomplete colonoscopy and 3 were unfit for colonoscopy. Panenteric capsule endoscopy completion rate (CECR) was 60.1% (65/108), SB CECR 86.1% (93/108) and colon CECR 71.3% (77/108). Colon CE bowel preparation was graded as good or excellent in 61.8%. 2 patients were excluded due to prolonged gastric retention of the colon capsule, 1 subsequently diagnosed with narcotic bowel syndrome. No complications were encountered. In the IBD group, 25 patients (61.0%) had evidence of active disease, leading to medication alterations in 21, surgery in 1 and conservative management in 3. Of the 16 patients in whom mucosal healing had been achieved, medication regimens were downgraded in 10 patients. In the suspected IBD group, this was identified in 13.4% (7 Crohns, 2 UC). Clinically relevant alternative findings included colon polyps (16), diverticular disease (9 colonic, 1 SB), angioectasia (6 SB, 1 colonic), and a small bowel carcinoid (1). The remaining 24 patients were diagnosed with functional bowel disorders and discharged. Of all the 34 patients with IBD identified, 22 had ileitis alone, 5 had ileocolonic disease and 7 had colonic disease alone. Conclusion: Panenteric capsule endoscopy is feasible and can be performed safely in patients known to have IBD. It can be used to guide management without resorting to conventional endoscopy and identifies pathology in all areas of the GI tract. Disclosure of interest: None Declared.